Worse off after knee replacements: How likely is it and what role does the pre-operative oxford knee score play? evidence from the English NHS - Pinedo Villanueva, R; Judge, A; Prieto Alhambra, D; Cooper, C; Arden, N (Elsevier, 2016)
Knee replacements are extremely effective surgical interventions associated with significant improvements in pain, function and quality of life. Although significant improvements have been reported in outcomes measures when comparing pre- and post-operative scores, little is known about how this improvement varies for different groups depending on the starting pain and function level. We aim to describe the changes in the Oxford Knee Score (OKS) and health-related quality of life (HRQL), and in particular to estimate the probability of a worse outcome, by decile of baseline OKS for patients in the English NHS.